Prevalence of osteoporosis in post-menopausal women in Melaka and 10 years' risk of developing fragility fracture - Muhammad Hafiz bin Hamzah (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
This is a cross-sectional study spanning over two-year (June 2015 until June 2017) period investigating post-menopausal women who did their Bone Mass Density (BMD) test at Hospital Melaka. The aim of this study is to determine the prevalence of osteoporosis among post-menopausal women, FRAX (Fracture Risk Assessment Tool) calculation to predict the average risk of fragility fracture in 10 years and relation of osteoporosis with ethnicity. 388 post-menopausal women age 45 to 90 years old were selected and all their BMD data and parameters were analyzed and used in FRAX calculation. The prevalence of osteoporosis among post-menopausal women in Melaka is 29.9%. More than half of patients had osteoporosis were Chinese (51%) followed by Malay (43%), Indian (5%) and Others (1%). The 10 years' average percentage of developing major osteoporosis is 10.81 ± 9.55 % while the average percentage of developing hip fracture is 4.20 ± 6.53 %. We conclude that the prevalence of the post-menopausal women who are osteoporotic is about 30% which is comparable to other countries (Japan, Egypt, Australia, Mexico, Argentina, and India). The 10 years' average percentage of developing major osteoporosis and hip fracture in our study is quite high with approximated around 20% and 10% respectively. We also found that Chinese ethnicity is having a higher percentage to get osteoporosis and 10 years' risk of developing fragility fracture.